2016
DOI: 10.1002/cam4.703
|View full text |Cite
|
Sign up to set email alerts
|

RRM1 *151A>T, RRM1 ‐756T>C, and RRM1 ‐585T>Gis associated with increased susceptibility of lung cancer in Chinese patients

Abstract: Ribonucleotide reductase M1 (RRM1) is a crucial gene in DNA repair. Recent studies have shown that RRM1 expression can be a powerful predictor of survival or chemotherapy sensitivity in patients presenting with carcinomas who are treated with adjuvant gemcitabine‐based chemotherapy including lung cancer. However, the relationship between the single nucleotide polymorphisms (SNP) of RRM1 and the susceptibility of lung cancer to chemotherapy has not been well addressed. We detected six tag SNPs of RRM1 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…We discovered that there was a potential binding site between PCBP2 and RRM1 through starBase website. Previous studies have proved the pivotal role of RRM1 in promoting DNA synthesis and repair (Mlak et al, 2018;Toth et al, 2017;Xu, Zheng, Mao, & Ling, 2016), thus we hypothesized that LINC02535 and PCBP2 might have boosting effects on RRM1, therefore promoting DNA synthesis and repair. RIP assay indicated that RRM1 mRNA was abundantly enriched in anti-PCBP2 group compared with anti-IgG group (Figure 5a).…”
Section: Linc02535 Cooperates With Pcbp2 To Enhance the Stability Of Rrm1 Mrnamentioning
confidence: 96%
“…We discovered that there was a potential binding site between PCBP2 and RRM1 through starBase website. Previous studies have proved the pivotal role of RRM1 in promoting DNA synthesis and repair (Mlak et al, 2018;Toth et al, 2017;Xu, Zheng, Mao, & Ling, 2016), thus we hypothesized that LINC02535 and PCBP2 might have boosting effects on RRM1, therefore promoting DNA synthesis and repair. RIP assay indicated that RRM1 mRNA was abundantly enriched in anti-PCBP2 group compared with anti-IgG group (Figure 5a).…”
Section: Linc02535 Cooperates With Pcbp2 To Enhance the Stability Of Rrm1 Mrnamentioning
confidence: 96%
“…RRM1 is the molecular target of gemcitabine, and its mRNA expression is related to the efficacy of gemcitabine therapy 33 . Xu et al found that the T/T+T/C genotypes of RRM1 rs11030918 increased susceptibility to lung cancer 34 . However, to date, the relationship between RRM1 rs11030918 and gemcitabine‐induced hematological toxicities has not been well addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also targeted by certain chemotherapeutics or used as a biomarker to predict their effectiveness 4446 . Furthermore, polymorphisms and altered expression of this gene have been linked to increased susceptibility to certain cancers 45,47 . RRM1 ’s role in cancer, however, is only discussed in terms of its involvement in DNA synthesis, and not in terms of telomere length regulation.…”
Section: Discussionmentioning
confidence: 99%